KrF Laser and Plasma Exposure of PDMS-Carbon Composite and Its Antibacterial Properties - Fajstavr, Dominik; Frýdlová, Bára; Rimpelová, Silvie; Kasálková, Nikola Slepičková; Sajdl, Petr; Švorčík, Václav; Slepička, Petr (Materials (Basel, Switzerland), 2022)
A polydimethylsiloxane (PDMS) composite with multi-walled carbon nanotubes was successfully prepared. Composite foils were treated with both plasma and excimer laser, and changes in their physicochemical properties were determined in detail. Mainly changes in surface chemistry, wettability, and morphology were determined. The plasma treatment of PDMS complemented with subsequent heating led to the formation of a unique wrinkle-like pattern. The impact of different laser treatment conditions on the composite surface was determined. The morphology was determined by AFM and LCM techniques, while chemical changes and chemical surface mapping were studied with the EDS/EDX method. Selected activated polymer composites were used for the evaluation of antibacterial activity using Gram-positive (Staphylococcus epidermidis) and Gram-negative (Escherichia coli) bacteria. The antibacterial effect was achieved against S. epidermidis on pristine PDMS treated with 500 mJ of laser energy and PDMS-C nanocomposite treated with a lower laser fluence of 250 mJ. Silver deposition of PDMS foil increases significantly its antibacterial properties against E. coli, which is further enhanced by the carbon predeposition or high-energy laser treatment.
Keywords: nanostructure; excimer laser treatment; E. coli; antimicrobial activity; carbon nanotubes; S. epidermidis; plasma treatment; wrinkle-like patterns; antibacterial properties; polydimethylsiloxane